2023
DOI: 10.34172/jrhs.2023.108
|View full text |Cite
|
Sign up to set email alerts
|

Trend Analysis of Homicide Mortality and Years of Life Lost in the South of Iran, 2004-2019

Abstract: Background: This study was conducted to determine the mortality rate and years of life lost (YLL) due to homicide in Fars province. Study Design: This was a cross-sectional study. Methods: All data related to deaths due to homicide in Fars province were obtained from the Populationbased Electronic Death Registration System. Crude and age-standardized mortality rate, YLL, and YLL rate data were calculated and joinpoint regression was used to examine the trend. Results: During 2004-2019, 2148 deaths due to homic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…When choosing among various methods for estimating YLL, researchers should consider the research objectives, the available data, and the model's flexibility. 5 In Iran, for example, this epidemiological method has been used to evaluate the burden of occupational injury, 17 homicide mortality, 18 drug-related deaths, 19,20 cancer mortality, 21,22 burn-related accidental deaths, 23 and the coronavirus disease 2019 (COVID-19). 24 A total of 19 268 complete suicide cases were registered in the Iranian FMO database from March 2016 to March 2020.…”
Section: Discussionmentioning
confidence: 99%
“…When choosing among various methods for estimating YLL, researchers should consider the research objectives, the available data, and the model's flexibility. 5 In Iran, for example, this epidemiological method has been used to evaluate the burden of occupational injury, 17 homicide mortality, 18 drug-related deaths, 19,20 cancer mortality, 21,22 burn-related accidental deaths, 23 and the coronavirus disease 2019 (COVID-19). 24 A total of 19 268 complete suicide cases were registered in the Iranian FMO database from March 2016 to March 2020.…”
Section: Discussionmentioning
confidence: 99%
“…If resources are limited, YLL may particularly help policymakers target premature death subpopulations and set top priorities for programs related to the prevention of premature death. 28 For example, uninformed and incorrect social attitudes toward the recreational use of prescription opioids may be a reason for the widespread use of drugs. Furthermore, despite the common belief that poisoning is solely the result of heavy alcohol or drug use, the findings of Yoon and colleagues’ study suggested that poisoning is more likely due to chronic substance use disorders and mood and anxiety disorders.…”
Section: Discussionmentioning
confidence: 99%